Mindfulness and its Relationship with Psychological Fitness among a Sample of High School Female Teachers in Makkah Al-Mukarramah (The International Journal for Scientific Research, 2023)
The study aimed to identify the relationship between Mindfulness and psychological fitness for a sample of High School Female Teachers in Makkah Al-Mukarramah, it also relied on the descriptive approach with its correlative and comparative methods. It was also conducted on a sample of (304) female teachers, and the two measures of Mindfulness and psychological fitness were applied to them, prepared by the researcher, after verifying their psychometric properties, which came in a very high degree, the researcher analyzed the data through the (SPSS)program, following appropriate statistical methods, It has reached many results, most notably: that the levels of Mindfulness and psychological fitness for a sample of High School Female Teachers in Makkah Al-Mukarramah are high, according to the responses of the sample members on the two scales. Also, there is a positive and statistically significant correlation at the level of significance (0.05), between the Mindfulness and the Psychological Fitness, there are also statistically significant differences at a significant level (0.05) between the mean scores of the sample members on the psychological fitness due to the marital status. In light of the results of the study, the researcher concluded by putting forward many recommendations and proposed future studies, which can contribute to strengthening the concept of Mindfulness and Psychological Fitness among teachers in educational institutions.
Keywords: Mindfulness; Psychological Fitness; Female Teachers; High School